2010
DOI: 10.1098/rspb.2010.1418
|View full text |Cite
|
Sign up to set email alerts
|

How resource quality differentially affects motivation and ability to fight in hermit crabs

Abstract: Contesting animals typically gather information about the resource value and that information affects fight motivation. However, it is possible that particular resource characteristics alter the ability to fight independently of the motivation. Using hermit crabs, we investigate how the resource in terms of shell quality affects both motivation and ability to fight. These crabs fight for shells, but those shells have to be carried and may impose physiological costs that impede fight vigour. We find that the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 44 publications
(74 reference statements)
0
16
1
Order By: Relevance
“…While long hiding times may be beneficial, there is a potential physical constraint on the maximum time for which a hermit crab may remain withdrawn into its shell. In the withdrawn position, a crab's access to fresh well-aerated seawater is restricted, which can constrain ventilation and hence aerobic respiration [67]. Some oxygen, however, will be available as oxyhaemocyanin (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While long hiding times may be beneficial, there is a potential physical constraint on the maximum time for which a hermit crab may remain withdrawn into its shell. In the withdrawn position, a crab's access to fresh well-aerated seawater is restricted, which can constrain ventilation and hence aerobic respiration [67]. Some oxygen, however, will be available as oxyhaemocyanin (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, where it becomes apparent that the resource is not worth fighting for relative to the anticipated costs of victory, persisting in the fight should not be the optimal strategy. Thus, as well as making appropriate tactical decisions, about which agonistic behaviours to use, making appropriate strategic decisions to 'cut one's losses' is also an ability that could increase with experience of real fights [62,63].…”
Section: (D) Appropriate Choice Of Tacticsmentioning
confidence: 99%
“…First, perceived RV could be updated during the fight, for instance, in situations where an intruder only comes into close contact with the resource once the fight is underway as in hermit crabs fighting over shells [62] or guppies fighting over shelters [63]. The ability to make such assessments can vary with experience [62,63]. Second, for contests that involve mutual assessment, the perceived costs of victory could be updated as increasing information about the opponent is gathered.…”
Section: (D) Appropriate Choice Of Tacticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples include vigilance and nest defense behavior (Bell et al 2010;Sirot 2012;Trnka and Grim 2013) and experimentally induced negotiation among chimpanzees (Pan troglodytes) in a cooperation experiment (Melis et al 2009). There have also been suggestions that hermit crabs (Paguroidea) negotiate over the exchange of shells when both indviduals can benefit from an improved fit (Hazlett 1978(Hazlett , 1996, but Doake and Elwood (2011) showed that it is not necessary to invoke negotiation processes to explain these exchanges. We here use the term negotiation for the exchange of signals in the context of cooperative interactions that by themselves are neither costly nor beneficial for the receiver, but potentially change the behavior of the receiver in favor of the sender.…”
Section: Introductionmentioning
confidence: 99%